2018
DOI: 10.5489/cuaj.5042
|View full text |Cite
|
Sign up to set email alerts
|

A new wave of urologists? Graduating urology residents’ practices of and attitudes toward social media

Abstract: Introduction: Social media (SoMe) have revolutionized healthcare, but physicians remain hesitant to adopt SoMe in their practices. We sought to assess graduating urology residents' practices of and attitudes toward SoMe.Methods: A close-ended questionnaire, employing five-point Likert scales, was distributed to all final-year residents (n=100) in Canadian urology training programs in 2012, 2014, and 2016 to assess SoMe usage and perceived usefulness. Results: All (100%) questionnaires were completed. Responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Our results also showed that more than half of the participants (67.3%) did not interact with patients using social media, and 57.5% of the participants did not discuss with patients the social media or the Internet usage. In relation to this matter, similar results have been observed in other investigation in which more than half of the respondents (59%) were opposed to employing social media for patient interaction [32].…”
Section: Discussionsupporting
confidence: 85%
“…Our results also showed that more than half of the participants (67.3%) did not interact with patients using social media, and 57.5% of the participants did not discuss with patients the social media or the Internet usage. In relation to this matter, similar results have been observed in other investigation in which more than half of the respondents (59%) were opposed to employing social media for patient interaction [32].…”
Section: Discussionsupporting
confidence: 85%
“…Bosslet et al (2011), Schweitzer et al (2012), Strausburg, Djuricich, Carlos, and Bosslet (2013), Kesselheim et al (2016), and Jain, Fervaha, Fuoco, and Leveridge (2018)…”
Section: Resultsmentioning
confidence: 99%
“…When the studies focused on the degree of participation in SM (i.e. in addition to having a profile, offering content or information), the results reflect that the residents are passive users of SM (Jain, Fervaha, Fuoco, & Leveridge, 2018; Maisonneuve, Chambe, Lorenzo, & Pelaccia, 2015). That is, residents more often look at content than provide it (Archambault et al, 2011, 2015).…”
Section: Presence and Use Of Smmentioning
confidence: 99%
“…Despite this enthusiasm and dramatic increase in usage, however, barriers exist because of the lack of clarity surrounding the appropriate use of social media within a professional setting. Moreover, despite multiple guidelines on use of social media in urology [7][8][9], fewer than 10% of graduating urology residents were aware of and had read them [10]. This is concerning in light of recent studies showing the unprofessional content present in publicly accessible social media pages for graduating urology residents and junior faculty [11].…”
Section: Introductionmentioning
confidence: 99%